Associations Between Racial Residential Segregation and Hypertensive Disorders of Pregnancy among Black women: The Coronary Artery Risk Development in Young Adults Study - Leah V. Dodds; Daniel J. Feaster; Kiarri N. Kershaw; Erica P. Gunderson; Tatjana Rundek; Michael Paidas; Tali Elfassy (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Introduction: Black women are at greater risk of hypertensive disorders of pregnancy (HDP). Racial residential segregation (RRS) drives racial health disparities. This study investigates the association between RRS and the onset of HDP among Black parous women in the U.S. Methods: The Coronary Artery Risk Development in Young Adults study is a cohort of Black and White adults aged 18–30 from four U.S. cities, recruited in 1985 and followed for over 30 years. RRS was measured using the local Getis-Ord Gi∗ statistic, categorizing neighborhoods as high (Gi∗ >1.96), medium (Gi∗ 0–1.96), or low (Gi∗ <0). Among Black women with at least one post-baseline pregnancy, HDP was self-reported as gestational hypertension, preeclampsia, or eclampsia. Generalized mixed models determined the association between RRS and HDP, for pregnancies (n = 941) nested within Black women (n = 598), and adjusting for age, follow-up time, time to pregnancy, education, income, BMI, physical activity, smoking, hypertension, baseline parity, and cumulative pregnancies. Results: The mean age was 23.1 years (SD: 3.6), with 22.7 % reporting HDP in at least one pregnancy. The cumulative incidence of HDP was 23.0 % in high, 20.6 % in medium, and 23.7 % in low RRS neighborhoods. Fully adjusted models showed no significant association between medium RRS (OR: 1.11; [95 % CI: 0.52, 2.40]) or low RRS (OR: 0.94; [95 % CI: 0.42, 2.16]) compared with high RRS and HDP. Conclusions: RRS was not associated with HDP among Black women. Future research should consider multifaceted factors through which racial segregation may relate to maternal outcomes.